Analysis of Mathematical Representation Ability of Grade VIII Students Reviewed from Self Efficacy in MTs Naming - Cahayanik, Cahayanik; Nurrahmawati, Nurrahmawati (EDUPEDIA Publisher, 2025)
This study aims to describe the ability of students' mathematical representation on the material of a two-variable linear equation system reviewed from Self Efficacy. The type of research used is qualitative research with descriptive methods. The sampling technique used is purposive sampling. The data collection technique used a test of students' mathematical representation ability, self-efficacy questionnaire, semi-structured interviews, and documentation. The data obtained was then analyzed in 3 stages, namely data reduction, data presentation and conclusion drawn. The results showed that students with a high self-efficacy category met all three indicators of mathematical representation ability, namely using visual representations to solve problems, solving problems by involving mathematical expressions and writing Steps to solve mathematical problems with words. Students with the category of self-efficacy Moderate meet two indicators of mathematical representation ability, namely using visual representation to solve problems and solve problems by involving mathematical expressions. Students with low self-efficacy meet one indicator of mathematical representation ability, namely solving problems by involving mathematical expressions. This study aims to describe the ability of students' mathematical representation on the material of a two-variable linear equation system reviewed from Self Efficacy. The type of research used is qualitative research with descriptive methods. The sampling technique used is purposive sampling. The data collection technique used a test of students' mathematical representation ability, self-efficacy questionnaire, semi-structured interviews, and documentation. The data obtained was then analyzed in 3 stages, namely data reduction, data presentation and conclusion drawn. The results showed that students with a high self-efficacy category met all three indicators of mathematical representation ability, namely using visual representations to solve problems, solving problems by involving mathematical expressions and writing Steps to solve mathematical problems with words. Students with the category of self-efficacy Moderate meet two indicators of mathematical representation ability, namely using visual representation to solve problems and solve problems by involving mathematical expressions. Students with low self-efficacy meet one indicator of mathematical representation ability, namely solving problems by involving mathematical expressions. This study aims to describe the ability of students' mathematical representation on the material of a two-variable linear equation system reviewed from Self Efficacy. The type of research used is qualitative research with descriptive methods. The sampling technique used is purposive sampling. The data collection technique used a test of students' mathematical representation ability, self-efficacy questionnaire, semi-structured interviews, and documentation. The data obtained was then analyzed in 3 stages, namely data reduction, data presentation and conclusion drawn. The results showed that students with a high self-efficacy category met all three indicators of mathematical representation ability, namely using visual representations to solve problems, solving problems by involving mathematical expressions and writing Steps to solve mathematical problems with words. Students with the category of self-efficacy Moderate meet two indicators of mathematical representation ability, namely using visual representation to solve problems and solve problems by involving mathematical expressions. Students with low self-efficacy meet one indicator of mathematical representation ability, namely solving problems by involving mathematical expressions. This study aims to describe the ability of students' mathematical representation on the material of a two-variable linear equation system reviewed from Self Efficacy. The type of research used is qualitative research with descriptive methods. The sampling technique used is purposive sampling. The data collection technique used a test of students' mathematical representation ability, self-efficacy questionnaire, semi-structured interviews, and documentation. The data obtained was then analyzed in 3 stages, namely data reduction, data presentation and conclusion drawn. The results showed that students with a high self-efficacy category met all three indicators of mathematical representation ability, namely using visual representations to solve problems, solving problems by involving mathematical expressions and writing Steps to solve mathematical problems with words. Students with the category of self-efficacy Moderate meet two indicators of mathematical representation ability, namely using visual representation to solve problems and solve problems by involving mathematical expressions. Students with low self-efficacy meet one indicator of mathematical representation ability, namely solving problems by involving mathematical expressions.